1997
DOI: 10.1097/00005537-199704000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Tracking of Patient's Head Movements During Computer‐Assisted Intranasal Microscopic Surgery

Abstract: A noninvasive system designed for patient tracking during image-guided intranasal sinus surgery is described. It is based on optical digitizing with a custom-made registration and reference system, locatable surgical instruments, and a self-localizing operating microscope. Experimental and clinical results reveal a high degree of accuracy for the system. A mean spatial error of 0.82 +/- 0.31 mm was determined for repositioning of the reference system in a plastic model of the skull. For the positioning of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 16 publications
0
31
0
1
Order By: Relevance
“…This system shows the 3-D virtual real image and has little error. Regarding the registration error using fiducial skin markers, early trials showed displacements from the CT data as large as 2 to 4 mm at the time of surgery, and this was concluded to be an unacceptable accuracy; thus, use of the noninvasive fiducial was inadequate [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This system shows the 3-D virtual real image and has little error. Regarding the registration error using fiducial skin markers, early trials showed displacements from the CT data as large as 2 to 4 mm at the time of surgery, and this was concluded to be an unacceptable accuracy; thus, use of the noninvasive fiducial was inadequate [12].…”
Section: Discussionmentioning
confidence: 99%
“…Computer-assisted surgery has been performed for cranial biopsies and tumor resections for two decades [6,12,13,21,24,26,34] before being introduced to the field of orthopaedics [1, 5, 8, 9, 11, 15-17, 19, 23, 29, 30]. Currently, navigation systems often use CT data to navigate pedicle screw applications [1,11,17], cup placements for hip arthroplasties [16], TKAs [8,19], and cruciate ligament reconstructions [9,23].…”
Section: Introductionmentioning
confidence: 99%
“…Although the more distant targets yielded slightly larger values, confirming the significant impact of the distance between the registration and target points on the accuracy [7,8,21], even the maximum deviation of 1.2 mm is still within the range (1 to 2 mm) that is often considered ''clinically acceptable'' for navigation system accuracy [1,21,25,26]. Maxillary splint-based systems with extraoral extensions for reference markers have been used previously with sufficient navigational accuracy in neurosurgery (0.29-0.86 mm [17], 0.0-2.0 mm [27]), in sinus surgery (1.56 AE 0.76 mm [28]), and in the temporal region (0.73 AE 0.25 mm [17,29]); however, only a few of these systems have been tested for targets in the lateral skull base region [15,29,30,31]. Bale et al used a mouthpiecebased registration template held in place by a vacuum system to successfully cannulate the foramen ovale [30], but did not test its applicability for Figure 3.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, depending on the size and weight of the extensions, the extraoral parts might act as a lever, leading to dislocation of the maxillary splint and poor registration accuracy. Additionally, extraoral support of the reference frame by the nasion or external auditory canal [28] is not advisable, as the attachment of reference structures to soft tissue tends to increase inaccuracy because of soft tissue deformity, a problem also known from non-rigidly mounted registration devices like headbands or headsets [32]. In an attempt to solve this problem, we took special care to make our dental splint device as lightweight and as small as possible.…”
Section: Discussionmentioning
confidence: 99%
“…Dental appliances such as occlusal splints and bite blocks have been proposed for use as positional reference devices [9,10]. For our purposes the standard occlusal splint was redesigned to maximise retention and stability with the aim of improved repeatability of placement.…”
Section: Image-to-physical Registration and Patient Trackingmentioning
confidence: 99%